In vitro and in vivo evaluatin of anti-diabetic and anti-inflammatory activity of asparagus aphyllus L., Crataegus azarolus L., and Ephedra alata Decne.: From traditional uses to cellular action mechanisms - Omer Kmail, Abdalsalam (CNRST, 2016)
There is a strong consideration that diabetes is accompanied by low grade inflammation. Both, diabetes and inflammation, lead to cardiovascular complications. Due to the well-known side- effects inherent in the available synthetic drugs presently used at clinics, there is a need for novel and efficient anti-diabetes and anti-inflammatory herbal-based drug candidates with reduced side effects. The aim of this study was to identify effective non-toxic anti-inflammatory as well as anti-oxidant and anti-diabetic medicinal plant extracts. Based on knowledge from traditional Greco-Arab and Islamic herbal medicine, we have selected three potential plants, Asparagus aphyllus L., (AA) Crataegus azarolus L., (CA) and Ephedra alata Decne. (EA). The first part of the study is focused on the extraction and assessment of cytotoxic and cytostatic effects of the plant extracts as well as in determination of non toxic concentrations of the plant extracts using both monoculture and coculture systems of cells from the hepatocyte cell line (HepG2) and cells from the monocyte cell line (THP-1) and their co-cultures. Both culture systems were treated with increasing concentration of the three plant extracts. Results obtained in this phase indicate that the three extracts are safe up to 125 μg/ml and that traditionally known anti-cancer properties of Crataegus azarolus L. and Ephedra alata Decne. extracts might be mediated, at least in part, through cytostatic effects. Furthermore, it seems that the observed increased cytostatic effects in the co-culture compared to monoculture system are mediated through macrophage-derived factors produced after activation of these cells by the plant extracts. The second part of the study is focused on the evaluation of antioxidant and anti-inflammatory properties of the plant extracts through measurements of pro-inflammatory and anti- inflammatory cytokines. Results obtained indicate that three plants extracts contain relatively high levels of phenols and significant antioxidant activities as measured with RP, DPPH, and ABTS. In addition to the observed significant antioxidant capacity, they regulate the production of pro-inflammatory as well as anti-inflammatory cytokines. The third part aimed to measure the anti-diabetic effects of plant extracts with positive anti- inflammatory effects through assessment of insulin secretion and GLUT4 translocation. The in vivo evaluation of hypoglycemic effects of five plant water/ethanol extracts showed that three plants exhibit potintial antidiabetic activities. Results obtained with GLUT4 Plasma membrane translocation assay and in vivo tests indicates that AA and AE plant extracts may downregulate blood glucose by improving GLUT4 membrane translocation in a concentration dependent manner at nontoxic concentrations. These experiments are steps forwards the identification of novel safe drugs for curing diabetes and inflammation by medicinal plants. Taken collectively, results obtained here using in vitro and in vivo test suggest that the traditionally known antidiabetic and anti-inflammatory properties of the three plants seem to be mediated, at least in part, through upregulation of GLUT4 plasma membrane translocation and downregulation of proinflammatory cytokine, respectively.
Keywords: Anti-inflammatory; Antidiabetic; Antioxidant; Cytotoxic; Cytotostatic; Asparagus aphyllus L; Crataegus azarolus L; Ephedra alata Decne.